Discussion Method to Enhance Creative Thinking Skills in Learning English at Madrasah Aliyah Singo Walisongo Magetan - Masruroh Masruroh; Fenty Andriani (STAI Ma'had Aly Al-Hikam Malang, 2023)
Creative thinking is the ability to analyze something based on data or information to generate new ideas in understanding something. One of the learning methods that is often used to improve creative thinking skills is the discussion method. The objective of this article is to describe the implementation of discussion method to enhance creative thinking skills in learning English at Madrasah Aliyah Singo Walisongo Magetan. This study applies a qualitative-descriptive approach. The data were collected using three data collection techniques covering observation, interviews, and documentation. The data obtained then analyzed using the theory from Moleong, which includes the processes of organizing data, summarizing data, and checking data validity. From the data analysis, it was found that the discussion method in learning English is effective to enhance creative thinking skills including preparing learning tools, understanding core competencies, basic competencies, learning objectives, mastering the material, active interaction between teacher and students, simplification of the material, making assessment benchmarks, and preparing class conditions. It is supported by students' interest in learning, facilities and infrastructure, teachers' sincerity and devotion, and discussion rules, while inhibiting factors include different characters, misuse of smartphones, and lack of support from parents. Overall, students are able to fulfill the characteristics of creative thinking skills such as flexibility, fluency, original thinking, elaboration, and evaluation skills.